Can CSR strategies increase the competitive advantage in the Ukrainian retail market? - Chesnok, Viacheslav (2010)
The focus of this research is in the area of Corporate Social Responsibility in the Ukrainian retail sector and the impact that CSR can create on the competitive position of the company. The research approach adapted in this dissertation includes an overview of recent Ukrainian history in the light of the complex processes that the country has been undergoing since the collapse of the Soviet Union. Dramatic change in the governance system has brought many issues that the country is trying to resolve. During the last decade the Ukrainian economy has moved from planned to market one and this gives ground to application of contemporary business concepts, including CSR. In order to assess a CSR potential the paper overview existing experience of local and international companies in the CSR field, their nature and outcomes and the role of the government. Three domains of CSR: Workplace, Community, and Marketplace have been selected as those with the strongest impact on business performance. Experience of the world leading companies as well as of Ukrainian actors is discussed. The findings of this research are based on secondary data derived from the research papers, in-depth semi-structured interviews with CSR consultants, and programmes conducted by METRO Ukraine, the European’s third largest retailer. The research revealed that CSR is at the initial stage of its development with key business actors reluctant to implement sustainable policies. However, a considerable potential can be realized if proposed programmes would be tailored to local conditions and mentality of stakeholders. Such study is important in order to examine the ways of how can business contribute to development of society and wellbeing and at the same time increase its competitiveness in the marketplace. The conclusion of the research considers a number of challenges and recommendations for the future development that emerged from the findings.